Nano‐Oil‐Barrier‐Based Fluttering Triboelectric Nanogenerator - Deokjae Heo; Jiwoong Hur; Hyeonho Cho; Kyunghwan Cha; Jaeung Choi; Moonhyun Choi; Jinkee Hong; Sunghan Kim; Sangmin Lee (Advanced Science)
Abstract In the field of triboelectric nanogenerators (TENGs), the application of a thin lubricant layer on the contact surface and its maintenance for long‐term cycling remain important challenges for improving the mechanical‐electrical stability of TENGs. Herein, a simple and innovative approach is proposed to solve this dilemma using commercial oil‐absorbing sheets and oil infusion steps. In particular, a wind‐driven nano‐oil‐barrier‐based fluttering triboelectric nanogenerator (NF‐TENG) is developed. The nano‐oil barrier (of nanoscale thickness) of NF‐TENG is thoroughly analyzed using atomic force microscopy imaging and electrical‐mechanical measurement/calculation results. Compared with other control groups, only NF‐TENG maintains 95% output performance from 100% initial output performance, and device damage is minimized even after 970,000 cycles. The mechanism of NF‐TENG and its differences from previous studies are established. NF‐TENG is optimized and studied for various design variables and wind speeds. NF‐TENG generated a peak power of 468 µW with 100 Hz and an average power of 166 µW at optimum load resistance, under a breeze wind speed of 6 m s−1. NF‐TENG demonstrates its applications in two real‐life scenarios: 1) wind harvesting at a rooftop vent pipe for outdoor temperature‐humidity sensing, and 2) wind harvesting during bicycle riding for safety light illumination.